KERJASAMA BADAN NARKOTIKA NASIONAL DENGAN UNITED NATIONS OFFICE ON DRUGS AND CRIME DALAM MENANGANI DRUG TRAFFICKING DI INDONESIA - Syifa Ul-ummah Ramadhani; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Narkoba is an abbreviation of narcotics, psychotropics and illegal drugs. The use of drugs can be carried out by being inserted into the human body either orally or by drinking, inhaled or injected which can change a person's thoughts, moods or feelings and behavior. The effects of these drugs will cause physical and psychological dependence. This drug abuse is mostly done by teenagers and adults who are initially tempted to feel pleasure for a moment or as an escape from the problems at hand, the impact of drug use can damage physical and mental health. Various efforts have been made by the Government of Indonesia in suppressing the circulation and abuse of drugs, one of which is the establishment of the National Narcotics Agency as a special institution to combat drug problems in Indonesia. Drugs are a transnational problem because their circulation is very wide, namely crossing national borders, so international cooperation is needed to deal with them. The National Narcotics Agency (BNN) cooperates with the United Nations Office on Drug and Crime (UNODC) to optimize its performance in eradicating drugs in Indonesia. This study uses the perspective of Liberalism and the Concept of International Cooperation to see the implementation of cooperation between BNN and UNODC. Data collection comes from books, journals, articles, websites and interviews. There are two findings in this study, namely international cooperation that resulted in an anti-drug resistance family intervention program. This program has a positive impact on increasing the ability of families to prevent drug abuse. Then there is an increase in capacity or capacity building for non-governmental organizations (NGOs) through family treatnet training. Keywords: BNN, drug trafficking, international cooperation, liberalism, UNODC.